EDUKASI GREEN ECONOMY DALAM PEMBENTUKAN GREEN ENTREPRENUERIAL BEHAVIOR PADA MAHASISWA - Damayanti, Damayanti; Oktariani, Mutiya (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
To empower communities, education is required to promote knowledge about the green economy. The core principle behind the green economy is to promote creative enterprise while maintaining stable environmental conditions. This research aims to find out and understand education green economy as an important thing in formation green entrepreneurial behavior for Economic Education students. The type of research used in this research uses qualitative research with a descriptive approach with data collection techniques in the form of observation, interviews, documentation and literature review. This research is motivated by the importance of education for changing paradigms and behavior so that always take every opportunity to seek information, learn and take action to protect and manage the environment. A thorough understanding of the green economy or green economy will encourage new ideas and an interest in entrepreneurship. The creation of ideas from difficult environmental situations, along with the need to survive, will give rise to the soul's survival via entrepreneurship. Thus, this research can assist students comprehend the green economy in order to build the character of green entrepreneurship among students majoring in economics education.